Systematic Review and Meta-Analysis of Rituximab for Steroid-Dependent or Frequently Relapsing Nephrotic Syndrome in Children - Gao, Xia; Wang, Yan; Xu, Zichuan; Deng, Huiying; Yang, Huabin; Zhong, Fu (Frontiers in Pediatrics, 2021)
Objective: To explore the effectiveness and safety of rituximab (RTX) for steroid-dependent or frequently relapsing nephrotic syndrome via a systematic review and meta-analysis. Methods: All the literature about RTX therapy for childhood nephrotic syndrome (NS) on PubMed, Web of Science, Cochrane Library, EMBASE, and Chinese biomedical literature database published before November 1, 2019, were conducted and selected according to the preset criteria. The Cochrane bias risk assessment tool was used to evaluate the quality of the literature included. The outcome data were analyzed by RevMan 5.3 software. Results: There were six RCT studies that met the inclusion criteria with a moderate quality after evaluation. At the end of the treatment, the relapse rate of NS in the RTX group reduced significantly when compared with that in the control group [odds ratio (OR) = 0.11, 95% confidence interval (CI) (0.03, 0.43), p = 0.001]. The number of patients in the RTX group used less steroid or/and calcineurin inhibitors significantly than that in the control group [OR = 0.05, 95% CI (0.01, 0.28), p = 0.0007]. For children who were steroid-dependent, RTX treatment significantly reduced the dosage of the steroid, compared with that in control [standardized mean difference (SMD) = −1.49, 95% CI (−2.00, −0.99), p < 0.00001]. There was no significant reduction in protein excretion between the two groups [SMD = −0.33, 95% CI (−0.71, 0.04), p = 0.08]. Fewer serious adverse reactions of RTX in the six studies were reported and most adverse events were mild. Conclusion: RTX is effective and safe for children with steroid-dependent or frequently relapsing nephrotic syndrome. Systematic Review Registration: Identifier: CRD 42020150933. https://www.crd.york.ac.uk/prospero/. This review has been registered to the PROSPERO on 27 Feb 2020.